The Correlation Between Junior High School Students’ Multimedia Engagement and Their Speaking Performance - Permatasari, Gita Ayu; Aminin, Zainul (Journal of English Language and Education, 2025)
In today's digital era, multimedia is readily accessible through digital platforms and serves as a resource of language acquisition. This study examines how junior high school students' engagement with multimedia, specifically English movies or English-language videos, influences their speaking performance. Therefore, this study aimed to investigate the correlation between junior high school students' multimedia engagement and speaking performance. A quantitative correlational design was employed to describe and quantify the degree of the correlation between junior high school students' multimedia engagement and their speaking performance. Participants included 96 students of ninth-grade students from MTSN 1 Kota Surabaya, selected by convenience sampling. Data were collected through two techniques: a questionnaire and a speaking performance test. The findings indicated that it rejected the null hypothesis and accepted the alternative hypothesis, which can be seen from the Pearson Product-Moment Correlation Analysis result of .789, with a p-value less than .001, indicating a high degree of positive correlation. It means that as students' multimedia engagement increases, their speaking performance also improves. This high positive correlation implies that students' engagement with multimedia, especially English movies or English-language videos, positively influences students' speaking performance.